2019
DOI: 10.18280/rcma.290202
|View full text |Cite
|
Sign up to set email alerts
|

Study of Some Parameters Influence on a Saharian Building Balance Sheet

Abstract: This work has undertaken a study of the influence of some parameters on the energy balance of a premise located in an arid area. The objective of this study is to calculate the heat of a South facing office record, and study the influence of various parameters such as: glazing, insulation, orientation, building materials and occupants. The system is composed of a desktop represented by its design, and external surrounding climatic condition of Bechar city.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…They also presented the effect of the number of these obstacles on the thermal behavior. Some other crucial numerical analyses on the thermohydraulic characteristics of solar channels with obstacles were reported in the literature Menni, Ghazvini, Ameur, Kim et al, 2020;Menni et al, 2022;Merabti et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…They also presented the effect of the number of these obstacles on the thermal behavior. Some other crucial numerical analyses on the thermohydraulic characteristics of solar channels with obstacles were reported in the literature Menni, Ghazvini, Ameur, Kim et al, 2020;Menni et al, 2022;Merabti et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…They experimentally tested the heat exchanger with N2 on the hotside at 600 °C and air on the cold-side at 38 °C. Other studies can be found in the literature as Menni et al [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%